Towards "green" viscoelastically prestressed composites: Cellulose fibre reinforcement. (1st December 2018) - Qin, Yang; Fancey, Kevin S.
Abstract: With growing concerns over environmental issues, fibre reinforced composites based on renewable, biodegradable low-cost cellulosic/cellulose fibres increasingly attract interest. This paper reports on the first study to produce viscoelastically prestressed polymeric matrix composites (VPPMCs) using regenerated cellulose/viscose continuous fibres. The aim was to demonstrate that this prestressing technique could improve the mechanical properties of a cellulose fibre reinforced composite without the need to increase section mass or thickness. By investigating the viscoelastic properties of cellulose yarn, a suitable load was applied to subject the fibres to tensile creep. The load was then released and the loose yarns were moulded into a polyester resin matrix. Following matrix solidification, the viscoelastically recovering fibres imparted compressive stresses to the matrix. The mechanical properties of these cellulose fibre VPPMCs were investigated by tensile, three-point flexural and Charpy impact tests. Under the creep conditions investigated, the VPPMC samples demonstrated up to 20% increase in tensile strength and modulus and a comparable improvement in flexural properties, compared with control (unstressed) counterparts. Nevertheless, the prestress effect reduced impact toughness by ∼30%, by impeding matrix crack formation and promoting fibre fracture. Based on findings from this paper, all-green VPPMCs may be achieved in the future by considering potentially suitable green resins.